1999
DOI: 10.1046/j.1365-2826.1999.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Expression of sst1 and sst2 Somatostatin Receptor Subtypes in the Arcuate Nucleus and Anterior Pituitary of Adults Rats

Abstract: The pattern of growth hormone (GH) secretion and rate of somatic growth are markedly sexually dimorphic, but the underlying neuroendocrine mechanisms are far from clear. In the present study, we tested the hypothesis that the sexual dimorphism of GH secretion may be due to gender-related differences in the transduction of somatostatin's actions in brain and/or pituitary. To accomplish this, we compared the distributional pattern and level of expression of two somatostatin receptor subtypes, sst1 and sst2, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
7
27
1
Order By: Relevance
“…These results are consistent with reports on rats (24,72) showing that the female PIT expresses less sst2 and sst5 compared with male PIT. Although the majority of sst subtypes were lower in the female PIT, the expression of sst1 was greater compared with males, as reported previously by others (55) but not observed by all (72). It remains to be determined what factors are responsible for these sex-dependent differences in SST/sst expression in the PIT.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with reports on rats (24,72) showing that the female PIT expresses less sst2 and sst5 compared with male PIT. Although the majority of sst subtypes were lower in the female PIT, the expression of sst1 was greater compared with males, as reported previously by others (55) but not observed by all (72). It remains to be determined what factors are responsible for these sex-dependent differences in SST/sst expression in the PIT.…”
Section: Resultssupporting
confidence: 93%
“…In fact, cell-specific regulation of SST expression is supported by the observation of some (11,20,28,41,42) but not all authors (5,26) showing that female rats and mice have lower immunodetectable SST in specific hypothalamic regions (i.e., median eminence, periventricular nucleus) compared with males, where these changes are associated with a reduction in SST mRNA levels in the periventricular nucleus but not in the arcuate nucleus. Also, Zhang et al (72) observed that sst1 mRNA-expressing cells were two-to threefold greater in the arcuate, but not in the ventromedial, nucleus of the HPT in males compared with female rats. Thus, future (neuro)anatomic studies in these animal models may help to unequivocally ascertain this apparent lack of sex-related differences in SST/ssts at the HPT and stomach levels.…”
Section: Resultsmentioning
confidence: 96%
“…ARC GHRH neurons express high levels of sst 1 and sst 2A mRNA . Both receptor proteins are present in the ARC, whereas other SRIF receptor subtypes are of low abundance in this area (Hervieu and Emson, 1998;Stroh et al, 2006;Kumar, 2007) (but see also Helboe et al, 1998), consistent with the involvement of sst 1 and sst 2 in the hypothalamic regulation of GH secretion (Guo et al, 1996;Zheng et al, 1997;Zhang et al, 1999;Lanneau et al, 2000).…”
Section: Introductionsupporting
confidence: 58%
“…Semiquantitative RT-PCR was used to determine whether SST and SSTR1-5 exhibited baseline sexual diergism in the mouse as reported previously for SSTR1 and 2 in rat (11), and whether the complete absence of SST would alter expression of the structurally related peptide CST or SSTRs in a sex-dependent pattern. There was a clear sexual diergism in SST gene expression in wild-type hypothalamus and pituitary gland; male mice had SST mRNA levels more than twofold those of female mice in both tissues, and no expression was detected in the Smst -/-mice (Table 1).…”
Section: Effects Of Sex and Genotype On Sst And Sstr Expressionmentioning
confidence: 99%
“…Furthermore, sexual diergism has been noted for expression of SSTR1, 2, 3, and 5 in the anterior pituitary and for SSTR1 but not SSTR2 in the rat hypothalamus (11)(12)(13). Although estrogen and testosterone both influence hypothalamic Smst gene expression and play a major developmental role in organizing the sexual diergism of GH secretion, the effect of gonadal steroids is not limited to the critical perinatal period of imprinting.…”
mentioning
confidence: 99%